PERAN KOMUNIKASI DALAM PENGEMBANGAN DAN PENERAPAN IPTEK DI INDONESIA - Deddy Mulyana (Jurnal Sosioteknologi, 2008)
Communication is used to both spread and develop science and technology. Communication technology can be used as a means of political propaganda, to change a concept, and move resources and an individual from one location to another. Some important values that we have to construct in communication are, among others, honesty (mutual trust) in determining a value system, in researching the cultural system of a community, in modifying information, and in spreading information. The obstacles in implementing a communication in Indonesia are that the Indonesian people have not yet had a blue print of their own cultural values and self concept, and many of them are information illiterate as well as still categorized as low-class or "kroco jiwa" individuals. (2006)